2022
DOI: 10.3389/fphys.2022.856590
|View full text |Cite
|
Sign up to set email alerts
|

Review of Processing Pathological Vectorcardiographic Records for the Detection of Heart Disease

Abstract: Vectorcardiography (VCG) is another useful method that provides us with useful spatial information about the electrical activity of the heart. The use of vectorcardiography in clinical practice is not common nowadays, mainly due to the well-established 12-lead ECG system. However, VCG leads can be derived from standard 12-lead ECG systems using mathematical transformations. These derived or directly measured VCG records have proven to be a useful tool for diagnosing various heart diseases such as myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 135 publications
0
13
0
Order By: Relevance
“…Our results differ from prior studies in that they account for a physiologically selected baseline using the TP segment as the true isolelectric/zero voltage and used the Kors transformation matrix to convert 12-lead ECGs into VCGs. The method of VCG construction can have a significant impact on subsequent measurements, 19,20 and data have demonstrated that the Kors transformation matrix, which is based on minimizing error between the 12-lead ECG and VCG rather than anatomic torso modeling, is superior to other transformations. 19,20 Compared to our results, Sur et al reported similar sex differences and similar mean SVG azimuth and elevation in a cohort of healthy patients with mean age ~40 ± 15 years, but the normal limits of SVG magnitude were significantly larger than our observed limits in this age range.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results differ from prior studies in that they account for a physiologically selected baseline using the TP segment as the true isolelectric/zero voltage and used the Kors transformation matrix to convert 12-lead ECGs into VCGs. The method of VCG construction can have a significant impact on subsequent measurements, 19,20 and data have demonstrated that the Kors transformation matrix, which is based on minimizing error between the 12-lead ECG and VCG rather than anatomic torso modeling, is superior to other transformations. 19,20 Compared to our results, Sur et al reported similar sex differences and similar mean SVG azimuth and elevation in a cohort of healthy patients with mean age ~40 ± 15 years, but the normal limits of SVG magnitude were significantly larger than our observed limits in this age range.…”
Section: Discussionmentioning
confidence: 99%
“…The method of VCG construction can have a significant impact on subsequent measurements, 19,20 and data have demonstrated that the Kors transformation matrix, which is based on minimizing error between the 12-lead ECG and VCG rather than anatomic torso modeling, is superior to other transformations. 19,20 Compared to our results, Sur et al reported similar sex differences and similar mean SVG azimuth and elevation in a cohort of healthy patients with mean age ~40 ± 15 years, but the normal limits of SVG magnitude were significantly larger than our observed limits in this age range. 18 This may be due to differences in study population and/or signal processing, as the ECGs used for that study were also recorded in the pseudo-orthogonal lead configuration (X, Y, and Z) rather than by transformation from 12-lead ECG and did not appear to undergo physiological baseline correction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VCG is a diagnostic method that provides information about the electrical activity of the heart, representing the vector's spatial orientation and magnitude at every moment [21]. The VCG can be extracted from the standard 12-lead ECG system in clinical applications, employing the VCG transformation matrices [22][23][24]. Kors regression transformation method (KRT), Inverse Dower transformation (IDT), Q Least Square Value Transformation (QLSV), P Least Square Value Transformation (PLSV), and Kors quasi-orthogonal transformation are some of the methods used to extract VCG from the measured ECG signals based on transformation matrices [22,23,25,26].…”
Section: Proposed Vcg Based Lead Fieldmentioning
confidence: 99%